Dysphagia and trismus: an unusual case of tetanus - Antonio Villa; Marianna Gregorio; Francesca Bassi; Alessandra Perego; Maria Francesca Donato; Vilma Galimberti; Maria Grazia Bellotti; Antonella Cheldi (Journal of Health and Social Sciences)
Tetanus is a life-threatening infection that is rare in the developed world; it is more frequent in the elderly people and immunocompromised patients. We report a case of a 53-year-old woman who presented with dysphagia, mouth pain and trismus. She did not report any injuries. The suspected diagnosis of tetanus was made. The blood examination showed severe lymphocytopenia and a positive result for the antinuclear antibody (ANA) test, with a suspected diagnosis of Sjogren’s syndrome. It is possible that her immunocompromised conditions could have led to the onset of tetanus, even after casual and minimal contact with Clostridium spores.